2020
DOI: 10.17392/1315-21
|View full text |Cite
|
Sign up to set email alerts
|

The challenge of the surgical treatment of paediatric distal radius/ forearm fracture: K wire vs plate fixation - outcomes assessment

Abstract: <p><strong>Aim</strong> <br />Distal radius/forearm fractures in adolescent patients remain challenging injuries to treat. Distal radius/forearm bony anatomy is not completely restored with intramedullary K wire fixation. The aim of this study was to compare radiographic and functional outcomes obtained using intramedullary K wire fixation and open reduction and internal fixation in the treatment of distal radius/forearm fracture.<br />&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Finally, poor was any other outcome or greater than 90 degrees loss of forearm rotation [9]. One of the studies reported functional outcomes in terms of objective quality of life and wrist function by employing different scoring parameters like the Mayo wrist score [14].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, poor was any other outcome or greater than 90 degrees loss of forearm rotation [9]. One of the studies reported functional outcomes in terms of objective quality of life and wrist function by employing different scoring parameters like the Mayo wrist score [14].…”
Section: Resultsmentioning
confidence: 99%
“…They are largely categorised by most authors into major and minor complications. Major complications include nonunion, delayed union, mal-union, and implant failure as mentioned in a number of studies [4,8,12,14]. On the other hand, this review refers to minor complications such as SSI, radial nerve palsy, as well as bursitis.…”
Section: Complicationsmentioning
confidence: 98%
See 1 more Smart Citation
“…ESIN application with a poller K-wire is a minimally invasive technique, and no delayed union or neurovascular damage was observed due to the application. OR-IF is recommended for older children because it provides more stable fixation and satisfactory reduction [ 12 ]. However, some complications could be seen, such as more extensive skin scars, slower healing, a high rate of refractures, and growth plate injury [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…It can lead to severe but rare complications such as growth plate disorder and iatrogenic fracture associated with these surgical techniques. Considering skeletal maturity, open reduction and internal fixation (OR-IF) are becoming popular in current practice in older pediatric cases [ 12 ]. In our clinical practice, although we prefer OR-IF in patients over 14 years of age or who have completed skeletal maturity, we use more minimally invasive intramedullary fixation methods in cases that have not completed skeletal maturity.…”
Section: Introductionmentioning
confidence: 99%